A Review on Minimally Invasive and Robotic Esophagectomy - Marco Taurchini; Antonello Cuttitta (Highlights on Medicine and Medical Research Vol. 13, 2021)
Esophageal cancer is the eighth most common cancer worldwide, and surgical resection remains the gold standard, not just in terms of having the best chance of cure, but also in terms of providing the best palliation for dysphagia. Esophagectomy is a complicated procedure that is associated with considerable morbidity and mortality rates of 23–50% and 2–8% in Western countries, respectively. At the moment no gold standard techniques exist for esophagectomy. The technique chosen is influenced by various of factors, the most relevant of which are the tumor’s location and the surgeon’s experience. In high-volume centres, minimally invasive esophagectomy (MIE) has been found to reduce the rate of complications while providing the same oncological outcome as open esophagectomy. The addition of robotic technique to MIE is relatively new and is gaining widespread acceptance. Robotic assisted minimally invasive esophagectomy (RAMIE) is a safe and effective procedure with comparable short-term outcomes to conventional MIE. To see if there is any meaningful benefit to using the robotic technique, randomised studies are needed. Esophagectomy is a time-consuming and complicated procedure that has a high rate of morbidity and mortality.